(untitled) (Research, Society and Development, 2022)
Population growth and, consequently, the uncontrolled growth of municipalities, increased demand for natural resources, inadequate disposal, and waste didisposalre factors significantly contribute to environmental degradation. In this context, an environment changes according to its degree of susceptibility, and this characteristic consists of the sensitivity it has to resist particular stress, thus being called vulnerability. In vulnerability analysis, natural (elevation, vegetation, soil type, etc.) and anthropic factors (land use, population density, etc.) are considered. To evaluate the factors most used in scientific works that deal with environmental vulnerability, a bibliographic survey was carried out using scientometrics and a bibliometric approach. The research base was SciVerse Scopus, and the search words were "Environmental Vulnerability" AND GIS* OR "Remote Sensing.”. Remote Control (SR) with Geographic Information Systems (GIS) combined with mathematical, and statistical analysis methods reduce the data size and generate more reliable results. The study also showed that, regardless of the technique used, environmental vulnerability analyzes have the same principle and variables, even though there is variation in the type and quantity of factors according to the region studied. Thus, there is no general rule for selecting the number of variables necessary for such an analysis.